Students' Misconceptions about Visual Arts and Technical in the Study of SSTVET in Bagabaga College of Education, Tamale - Mumuni Zakaria Fusheini; Adams Abudi (Social Education Research, 2022)
This study examined misconceptions held by first-year students of Bagabaga College of Education regarding the Visual Arts and Technical Education components of the Foundations of Social Studies and Technical Vocational Education and Training (FFSSTVET) subject. An Action Research design was employed to gather data, which were analyzed using thematic and narrative analyses. A census sampling technique was used, including all 550 Level 100 students enrolled in the FFSSTVET course. Data were collected at three stages and analyzed thematically. At the pre-intervention stage ('before lessons'), students demonstrated limited understanding of the nature of Visual Arts and Technical Education in colleges. During the intervention stage ('during lessons'), students expressed interest in pursuing Visual Arts and Technical programs after learning about the subjects and associated career opportunities. At the post-intervention stage ('after lessons'), many students without a Visual Arts and Technical background opted to change their programs from Maths, English, and Early Childhood Education to Visual Arts and Technical programs. The study concluded that inadequate orientation at basic and secondary school levels contributes to students' misconceptions about Visual Arts and Technical Education. Therefore, it is recommended that Technical Vocational Education and Training (TVET) stakeholders implement regular outreach programs to educate students at the basic and secondary school levels about the benefits of TVET education in developing entrepreneurial skills and addressing unemployment in Ghana.